Modeling the Effect of Stress and Stigma on the Transmission and Control of Tuberculosis Infection - Lengiteng, Lalashe; Kajunguri, Damian; Nkansah-Gyekye, Yaw (Technology, and Sciences, 2016)
In this paper a continuous time deterministic model with health education campaign and treatment strategy is formulated to assess the effect of stress and stigma on the transmission and control of Tuberculosis (TB). The effective reproduction number eℜis obtained and used to investigate the impact of health education campaign and treatment strategies. The effective reproduction numbers for health education campaign and treatment considered separately were found not to be effective as compared to a combination of both strategies. Numerical simulation results show that TB can be reduced or eliminated from the community when 10<ℜas treatment is applied. The disease prevalence and incidence are high when stigma is high and decline gradually when the combination of both treatment and health campaign are administered. We recommend that health education campaign to reduce stress among individuals and stigma for infectious individuals should be accompanied by treatment of active TB individuals for improved reduction of TB disease.
Keywords: Tuberculosis; Stress; Stigma; Effective reproduction number; simulations